War against the COVID-19 pandemic: reflection in light of Florence Nightingale's nursing theory - Andréia Guedes Oliva Fernandes; Talita de Cássia Raminelli da Silva (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To reflect on the relationship and importance of the environmental theory regarding practices for promotion, prevention, and treatment of COVID-19. Methods: A theoretical-reflexive study about the COVID-19 pandemic in light of the environmental theory proposed by Florence Nightingale. Results: It is observed that the application of the theoretical foundations proposed by the environmental theory is related to the current practices used in the fight against the COVID-19 pandemic. Final Considerations: It is believed that the theoretical basis is fundamental for the critical-reflexive training of the nursing professional, for the consolidation of Nursing as a science; therefore, it could provide a foundation in nowadays battle against the pandemic.